Research on the Employment Difficulties of College Students in China Based on the Epidemic Situation - Ge, Di (Transactions on Social Science, Education and Humanities Research, 2023)
The employment issue of college students is closely related to people’s livelihoods and social stability, and is a highly concerned social issue. Under the special background of the COVID-19, the employment problem of college students in China is prominent, which is mainly reflected in the decline in the employment rate of college students and the serious layoffs of employers. The article analyzes the employment problem of college students from three aspects: economic development status, changes in market demand, and supply level of college students. Suggestions are put forward from several aspects such as government policy support, active cooperation between the market and universities, and the establishment of correct employment and career choices by college students.